Population Stress Reactions in North-East Hungary during the Pandemic (European Journal of Marketing and Economics, 2021)
Emergency caused by the SARS-CoV-2 has provoked several difficulties in daily life. On the other hand, it provided an opportunity to produce new attitudes toward our life and community, but also forced us to face our vulnerabilities. Outbreak of the SARS-CoV-2 highlighted that despite our vulnerability, we can manage this crisis, by being able to influence our stress reaction as well as our fears and emotions about the pandemic. Faculty of Healthcare of the University of Miskolc is training such professionals, whose priority task is to preserve the mental health of individuals and communities, reduce stress reactions, increase the available information on the subject, and help the community to adapt adequately to unexpected difficulties, like a pandemic situation. In the present study, we examined the mental state of the population of Northeastern Hungary in the second wave to adapt the above-described education to the ongoing changes caused by the pandemic. During the research, we applied an online questionnaire, that included the Hungarian version of the 10-item Perceived Stress Scale-, the Adult Hope Scale-, the WHO Well-Being, and the Buss Perry aggression questionnaire. Most participants (n=528) live in small towns or villages and their average age is 39.4±13.1. The aggression level of responders did not reach the threshold, but the level of verbal aggression exceeded it. The participants were more stressed, but they thought they could handle their problems. Consequently, the pandemic harms the mental state and health of the population, therefore the presence of health professionals is needed.
Keywords: pandemic, stress, aggression, subjective Well-Being, online questionnaire